Development of Electronic Student Work-Sheets (E-LKPD) by Digital Drawing Mode at Private Vocational Schools - Meilisa, Meilisa; Tristantie, Nining; Nitami, Dita Dwi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
This research emerged from several obstacles in the field, namely students' difficulties in understanding digital technical design material with Ibis Paint. The aims of this research are : 1) to develop an E-LKPD for digital fashion drawing at Private Vocational School, 2) to determine the feasibility of a digital fashion drawing E-LKPD. This research used the RD method with a 4-D development model (define, design, development, and disseminate). The validation and trial stages were carried out to assess the feasibility of E-LKPD. Material experts and media experts play a role in validation to obtain input regarding the appropriateness in terms of material and media. The feasibility test was carried out through a questionnaire to class XI students at Setia Budi Binjai Private Vocational School, second semester. Data analysis uses a five-scale score (Likert scale) for the predetermined assessment categories. The results of this research are: 1) validation of E-LKPD drawing mode according to material experts